2017
DOI: 10.1016/j.gie.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after liquid nitrogen spray cryotherapy in Barrett's esophagus–associated high-grade dysplasia and intramucosal adenocarcinoma: 5-year follow-up

Abstract: Background Liquid nitrogen spray cryotherapy (LNSCT) has been shown to be a safe, well-tolerated, and effective therapy for Barrett’s esophagus (BE)-associated high grade dysplasia (BE-HGD) and intramucosal adenocarcinoma (IMC). Long-term follow-up is lacking. Aims The authors’ aim was to assess the efficacy, durability, and rate of neoplastic progression after LNSCT in BE-HGD/IMC at 3 and 5 years. Methods In this single-center, retrospective study drawn from a prospective database, patients with BE-HGD/IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…The eradication response appears to be durable for up to 5 years. Over a follow up period of 5 years in 40 patients with HGD or EAC, complete remission of HGD, CE-D and CE-IM was seen in 93%, 88% and 75% of patients respectively[ 30 ]. Incidence of recurrent HGD/EAC was 1.4% per person years.…”
Section: Cryospray With Liquid Nitrogenmentioning
confidence: 99%
“…The eradication response appears to be durable for up to 5 years. Over a follow up period of 5 years in 40 patients with HGD or EAC, complete remission of HGD, CE-D and CE-IM was seen in 93%, 88% and 75% of patients respectively[ 30 ]. Incidence of recurrent HGD/EAC was 1.4% per person years.…”
Section: Cryospray With Liquid Nitrogenmentioning
confidence: 99%
“…Since the development and initial clinical use of esophageal cryotherapy in 1999 22 , studies in treatment-naive patients have demonstrated encouraging efficacy, safety, and durability 18 23 24 25 . In addition, because it can be applied to non-lifting and nodular tissue, cryotherapy has become increasingly popular as a salvage modality when patients are not candidates for, or have experienced suboptimal response to EMR, RFA, or the combination.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is a true RFA failure cohort as the patients included in this study had persistent intestinal metaplasia and/or dysplasia after at least four RFA procedures before being deemed a RFA failure (median RFA treatments was five). In addition, this is an initial efficacy and feasibility study and, as such, long‐term durability data are not provided here as in most initial efficacy and feasibility studies, as opposed to long‐term durability studies in cryotherapy and RFA The centers included in the present study are high‐volume BE referral centers with similar RFA and cryotherapy techniques and protocols, which limit the heterogeneity of the study. Finally, RFA failures are uncommon, as RFA is usually clinically successful.…”
Section: Discussionmentioning
confidence: 99%